Fatigue behaviour of AA6082-T6 MIG welded butt joints improved by friction stir processing - Silva, J. da (2013)
Friction Stir Processing (FSP) was based on the principles of Friction Stir Welding (FSW), a solid-state joining process originally developed for aluminium alloys. It is an emerging metalworking technique which can provide localized modification and control of microstructures in near-surface layers of processed metallic components. In this research, FSP appears as an alternative to traditional methods for fatigue strength improvement of weld joints, such as re-melting, hammering and blasting. This technique was applied on Metal Inert Gas (MIG) butt welds with and without reinforcement, performed on AA6082-T6 alloy plates. The potential benefits of post-processing MIG welds by FSP were studied using microstructure analysis, hardness measurement, tensile strength, residual stress measurement, and fatigue testing. Fatigue tests were carried out under constant amplitude loading with the stress ratio R set to 0. Friction stir processing of MIG welds does not change the hardness and mechanical strength of the weld substantially, but the fatigue strength was increased, due to the geometry modification in the weld toe, reduction of weld defects and grain refinement of the microstructure.